2017
DOI: 10.1016/j.molcel.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Transcription without XPB Establishes a Unified Helicase-Independent Mechanism of Promoter Opening in Eukaryotic Gene Expression

Abstract: Transcription starts with the assembly of pre-initiation complexes on promoters followed by their opening. Current models suggest that class II gene transcription requires ATP and the TFIIH XPB subunit to open a promoter. Here, we observe that XPB depletion surprisingly leaves transcription virtually intact. In contrast, inhibition of XPB ATPase activity affects transcription, revealing that mRNA expression paradoxically accommodates the absence of XPB while being sensitive to the inhibition of its ATPase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 42 publications
3
85
1
Order By: Relevance
“…On the other hand, TFIIH binds downstream of the TSS and has been proposed to push DNA into the RNAP cleft through its helicase/translocase activities and the torsional strains in DNA promote DNA opening. However, a recent study shows that the ATPase activity of TFIIH subunit XPB is only required to relieve the auto-inhibition imposed by XPB, not DNA melting itself (Alekseev et al., 2017). It therefore remains to be seen how DNA melting and opening occur in RNAPII.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TFIIH binds downstream of the TSS and has been proposed to push DNA into the RNAP cleft through its helicase/translocase activities and the torsional strains in DNA promote DNA opening. However, a recent study shows that the ATPase activity of TFIIH subunit XPB is only required to relieve the auto-inhibition imposed by XPB, not DNA melting itself (Alekseev et al., 2017). It therefore remains to be seen how DNA melting and opening occur in RNAPII.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, the yeast Pol II CC shows signs of DNA melting in the absence of TFIIH [24]. This led to the hypothesis that all three eukaryotic Pols use a similar mechanism of promoter opening where the Pols and initiation factors have an intrinsic ability to melt DNA without ATP [24]. This fits well with the model presented for Pol I, which has likely evolved an efficient means to melt Pol I promoter DNA without the help of ATP-dependent translocases [35].…”
Section: Promoter Openingmentioning
confidence: 55%
“…Recent results with human TFIIH showed that XPB helicase ATPase activity is dispensable for Pol II transcription as global initiation is relatively unaffected upon XPB deletion [24]. In agreement with this, the yeast Pol II CC shows signs of DNA melting in the absence of TFIIH [24].…”
Section: Promoter Openingmentioning
confidence: 68%
See 1 more Smart Citation
“…Another small molecule that targets XPB is spironolactone, which appears to selectively degrade the XPB protein while retaining the structural integrity of the rest of the TFIIH complex . This led to the provocative conclusion that, contrary to existing models, XPB function was not generally required for pol II transcription in human cells . Because XPB requires continual ATP hydrolysis to maintain an open DNA template, these findings suggested a unified mechanism of promoter opening from bacteria to mammalian cells that does not require ATP hydrolysis.…”
Section: Small Molecule Inhibitors Of Tfiih Functionmentioning
confidence: 99%